A hypothetical role for autophagy during the day/night rhythm‐regulated melatonin synthesis in the rat pineal gland. Issue 1 (17th May 2021) - Ge, Wei; Yan, Zi‐Hui; Wang, Lu; Tan, Shao‐Jing; Liu, Jing; Reiter, Russel J.; Luo, Shi‐Ming; Sun, Qing‐Yuan; Shen, Wei
Abstract: Melatonin is a highly conserved molecule that regulates day/night rhythms; it is associated with sleep improvement, reactive oxygen species (ROS) scavenging, anti‐aging effects, and seasonal and circadian rhythms and has been a hot topic of research for decades. Using single‐cell RNA sequencing, a recent study describes a single‐cell transcriptome atlas for the rat pineal gland. Based on a more comprehensive analysis of the retrieved data (Mays et al., PLoS One, 2018, 13, e0205883), results from the current study unveiled the underappreciated gene regulatory network behind different cell populations in the pineal gland. More importantly, our study here characterized, for the first time, the day/night activation of autophagy flux in the rat pineal gland, indicating a potential role of autophagy in regulating melatonin synthesis in the rat pineal gland. These findings emphasized a hypothetical role of day/night autophagy in linking the biological clock with melatonin synthesis. Furthermore, ultrastructure analysis of pinealocytes provided fascinating insights into differences in their intracellular structure between daytime and nighttime. In addition, we also provide a preliminary description of cell‐cell communication in the rat pineal gland. In summary, the current study unveils the day/night regulation of autophagy in the rat pineal gland, raising a potential role of autophagy in day/night‐regulated melatonin synthesis.